2021
DOI: 10.3390/cancers13164023
|View full text |Cite
|
Sign up to set email alerts
|

PSMA Theranostics: Current Landscape and Future Outlook

Abstract: Introduction: Prostate-specific membrane antigen (PSMA) is a promising novel molecular target for imaging diagnostics and therapeutics (theranostics). There has been a growing body of evidence supporting PSMA theranostics approaches in optimizing the management of prostate cancer and potentially altering its natural history. Methods: We utilized PubMed and Google Scholar for published studies, and clinicaltrials.gov for planned, ongoing, and completed clinical trials in PSMA theranostics as of June 2021. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 86 publications
(109 reference statements)
0
33
0
Order By: Relevance
“…In mRCC patients with high PSMA avidity, another future perspective is represented by Radioligand Therapy. In a theranostic approach, mRCC could be first imaged with PSMA PET/CT and subsequently treated with PSMA labeled with β-emitting (such as 177 Lu or 90 Y) or α-emitting (such as 225 Ac) radionuclides, as it happens today for neuroendocrine tumors and prostate cancer (Zhang et al 2021 ; Uccelli et al 2021 ). This approach could be particularly useful in chrRCC, where PSMA expression is usually high and therapeutic options are limited (Baccala et al 2007 ; Spatz et al 2018 ; Toyama et al 2021 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…In mRCC patients with high PSMA avidity, another future perspective is represented by Radioligand Therapy. In a theranostic approach, mRCC could be first imaged with PSMA PET/CT and subsequently treated with PSMA labeled with β-emitting (such as 177 Lu or 90 Y) or α-emitting (such as 225 Ac) radionuclides, as it happens today for neuroendocrine tumors and prostate cancer (Zhang et al 2021 ; Uccelli et al 2021 ). This approach could be particularly useful in chrRCC, where PSMA expression is usually high and therapeutic options are limited (Baccala et al 2007 ; Spatz et al 2018 ; Toyama et al 2021 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…PSMA imaging may theoretically serve as a biomarker for assessing treatment response. However, this application may face significant challenges since PSMA avidity can be affected by several factors (e.g., castration sensitivity, timing and type of therapy, or lesion localization) [ 31 ]. According to the consensus statement on the PSMA PET/CT response criteria, patients with hormone-sensitive prostate cancer should not undergo this imaging modality within the first three months of systemic therapy [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its good physical properties and the possibility of post-treatment imaging, 177 Lu labeled PSMA has been extensively studied and it has emerged as a novel treatment for mCRPC. Until recently, the majority of PSMA-targeting tracers involve urea-based agents (small molecule inhibitors) including 177 Lu-PSMA-I&T (imaging and therapy) and 177 Lu-PSMA-617, with the latter being preferred due to lower renal uptake [ 102 , 103 ]. A previous study of Ruigrok et al revealed that although 177 Lu-PSMA-617 and 177 Lu-PSMA-I&T show similar binding characteristics in prostate tumors, 177 Lu PSMA-I&T has a lower tumor-to-kidney ratio than 177 Lu PSMA-617 [ 104 ].…”
Section: Psma-targeted Radionuclide Therapymentioning
confidence: 99%